2018
DOI: 10.1007/s10661-018-6748-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the efficiency of polar and non-polar solvents in oil sludge recovery using solvent extraction

Abstract: Oily sludge is a stable emulsion of water in oil, containing solid particles, oily hydrocarbons, and metals with different compositions, which is greatly hazardous to the environment; as a consequence, they must be removed or recovered. Recovery methods are usually preferable because of the possibility of valuable oily hydrocarbons recovery as well as environmental protection. Liquid extraction is one of the most effective methods of oily sludge recovery. In this research, hydrocarbon recoveries from oily slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 20 publications
2
20
1
1
Order By: Relevance
“…Also, cyclohexane had high ORR values at 2:1 C/OS ratio with Triton X-114 (63% ± 3) and rhamnolipid (63% ± 2). These values are higher compared to other studies (Biceroglu 1994;Avila-Chavez et al 2007;Zubaidy and Abouelnasr 2010;Hu et al 2015;Hu et al 2017;Nezhdbahadori et al 2018). These authors reported ORR values lower than 60%.…”
Section: Resultscontrasting
confidence: 64%
“…Also, cyclohexane had high ORR values at 2:1 C/OS ratio with Triton X-114 (63% ± 3) and rhamnolipid (63% ± 2). These values are higher compared to other studies (Biceroglu 1994;Avila-Chavez et al 2007;Zubaidy and Abouelnasr 2010;Hu et al 2015;Hu et al 2017;Nezhdbahadori et al 2018). These authors reported ORR values lower than 60%.…”
Section: Resultscontrasting
confidence: 64%
“…High equipment cost, complicated operation and non-continuous operation have become the main obstacles hindering the development of this method. On the other hand, oil recovered directly cannot be used directly, and further refining is still needed, which increases the processing cost and cycle [68,69].…”
Section: Technical Advantages Of Oily Sludge Pyrolysismentioning
confidence: 99%
“…The strategies to treat these wastes are based on contaminant reduction or oil recovery techniques. Following the current waste management trends that indicate the importance of waste reduction, reuse and recycle (Sakai et al 2011;European Parliament 2008), the treatment of oil sludges has been recently aimed at oil recovery techniques (Gumerov et al 2017;Nezhdbahadori et al 2018). Therefore, oil sludge washing (OSW) with surfactants has been applied to treat the oil sludges as an oil recovery method (Zhang et al 2012;Liang et al 2017;Duan et al 2018;Liu et al 2018a), and co-solvents can be added to enhance the extraction of the oil (Hwa et al 2016;Kuppusamy et al 2017).…”
Section: Introductionmentioning
confidence: 99%